The core of negative symptoms in schizophrenia: affect or cognitive deficiency? - Mundt, Christoph; Barnett, Winfried; Witt-Schneider, Gabriele (Psychopathology, 2010)
The association of negative symptoms on one hand and cognitive failures and language and thought disturbances on the other hand was examined in 25 schizophrenics and 22 neurotics over a 2-month period of intensive therapy. Psychopathological negative symptoms were more pronounced in schizophrenics than in neurotics at the first assessment before intensive therapy. However, cognitive and language performance showed no difference between the groups in both cross-sectional comparisons before and after treatment. Thus, our hypothesis that cognitive deficiencies are the core of negative symptoms could not be confirmed. It is discussed that young schizophrenics at an early stage of the illness may imply more affective components in the psychopathology of their negative syndrome than chronic schizophrenics with more pronounced cognitive deficits.
Published online: February 10, 2010
Gesehen am 09.12.2020